Study on effect of the inner vortex finder length on the flow properties of the hydrocyclone with double vortex finders - Yuekan Zhang; Peikun Liu; Xinghua Yang; Junru Yang; Linjing Xiao (Functional Materials, 2016)
The traditional hydrocyclone can only obtain two products: overflow and underflow. In the paper, we propose three-products hydrocyclone with double vortex finders. The hydrocyclone is designed with two coaxial overflow tubes with different diameters. During overflow, light and fine particles exit from the inner overflow tube. The mid-size particles overflow from the outer overflow tube, and the coarse particles through the underflow pipe. Therefore, one classification can obtain three different narrow-grade-classification products. The inner vortex finder length is the important influent factor on the flow performance of the hydrocyclone. This paper is mainly focused on the study of the flow field of both the air and the liquid phase, and of the effects of the inner vortex finder length on the velocity field, pressure field and the air column of the hydrocyclone with double vortex finders.